Methylation of UHRF1 by SET7 is essential for DNA double-strand break repair. Issue 1 (24th October 2018) - Hahm, Ja Young; Kim, Ji-Young; Park, Jin Woo; Kang, Joo-Young; Kim, Kee-Beom; Kim, Se-Ryeon; Cho, Hana; Seo, Sang-Beom
Abstract: Ubiquitin-like with PHD and RING finger domains 1 (UHRF1) is a key epigenetic regulator of DNA methylation maintenance and heterochromatin formation. The roles of UHRF1 in DNA damage repair also have been emphasized in recent years. However, the regulatory mechanism of UHRF1 remains elusive. In this study, we showed that UHRF1 is methylated by SET7 and demethylation is catalyzed by LSD1. In addition, methylation of UHRF1 is induced in response to DNA damage and its phosphorylation in S phase is a prerequisite for interaction with SET7. Furthermore, UHRF1 methylation catalyzes the conjugation of polyubiquitin chains to PCNA and promotes homologous recombination for DNA repair. SET7-mediated UHRF1 methylation is also shown to be essential for cell viability against DNA damage. Our data revealed the regulatory mechanism underlying the UHRF1 methylation status by SET7 and LSD1 in double-strand break repair pathway.